Making Publics, Making Places - Barbour, Kim; Griffiths, Mary; Barbour, Kim; Griffiths, Mary (University of Adelaide Press, 2016)
This book focuses on the surprising generative possibilities which digital and smart technologies offer media consumers, citizens, institutions and governments in making publics and places, across topics as diverse as Twitter audiences, rural news, the elasticity of the public sphere, Weibo, cultural heritage and responsive spaces in smart cities. Multidisciplinary perspectives engage with critical questions in new media scholarship. General readers, curious about how technologies are enabling social, public and civic participation, will enjoy the book$1 (Bs mix of fresh approaches and insights.s
English
Keywords: Communication studies; rowan wilken; jill mackenzie; public audiencing; generative technologies; ying yiang; opinion leader; mitchell harrop; social media; kathryn bowd; find your adelaide; cultural heritage; high speed broadband; publics; smart buildings; weibo; twitter; elasticity of the public sphere; nbn; unesco; graphic narratives; smart cities; public participation; fragmenting audiences; places; kim barbour; aaron humphrey; responsive places; mary griffiths; darren peacock; spaces; jenny kennedy; maria cristina paganoni; bjorn nansen; picturing placelessness; john budarick; wilfred wang; tyranny of distance; Guangzhou; Sina Weibo